Peran Sektor-Sektor Ekonomi Terhadap Pertumbuhan Ekonomi Kabupaten Halmahera Utara - Huzaima Abdullah; Musdar Muhammad; Firdaus Duko (OPTIMAL Jurnal Ekonomi dan Manajemen, 2024)
One of the other objectives of economic development is to create jobs needed by the community, thereby reducing unemployment and directly increasing national income and also encouraging economic growth. Research objectives; To find out what economic sectors are the basic sectors and non-basic sectors, to increase economic growth in North Halmahera district. The research location is North Halmahera district, using the method, quantitative description, with analytical tools that use Location Quotient (LQ), secondary data time sires 2019-2023. The results of the study; the basic sector, as many as fourteen economic sectors, the agriculture, forestry and fisheries sector and the water supply sector, waste management, waste and recycling, these two sectors are very dominant in providing economic growth in North Halmahera district, in addition to being a basic sector also exports, while the manufacturing industry sector and the company services sector, this sector is unable to meet the needs within the North Halmahera district area, so to meet the needs imported from other regions.